A field study aiming to determine entrepreneurial profiles of university students (Examples of Dumlupinar University - Inönü University) - Acet, Mehmet; Serdar Yücel, A.; Kalkavan, Arslan; Yilmaz, Nurkan (My University, 2014)
Element of entrepreneurship had an important role in ensuring the social welfare and in regional development in the 21st century. In this sense, universities undertaking the mission of educating future?s entrepreneurs bear tremendous responsibility. It is obligatory to determine the university students? tendency of entrepreneurship, and to guide correctly those having entrepreneurship characteristics and bring them in to the business life. In this study, it is aimed to determine entrepreneurship profiles of students receiving education in different faculties/ departments; and to compare certain demographical characteristics of students educated in School of Physical Education and Sports (S.P.E.S.) with the characteristics of students participated in the research and receiving education in other faculties. Also the effects of total time of doing sports and status and period of registered sporting on the entrepreneurship profiles of participants were examined. Research was made practically on 479 students receiving education in "Faculties of Education, Economic and Administrative Sciences, and School of Physical Education and Sports" who were elected by means of random sampling method. 247 female and 232 male students participated in the research. At the end of the study, it is determined that infrastructure of entrepreneurship of the university students is at a satisfactory level, and that entrepreneurship level did not differ according to the variables of gender and age. It is found that students with a monthly income ? 500 TL have a lower entrepreneurship level in comparison to the other income groups, and students who are doing sports and have a social-extravert and active psychological structure have a higher entrepreneurship level. Also, it is established that students of school of physical education and sports have the highest entrepreneurship level according to the variable of faculty and department. © 2014 AENSI Publisher All rights reserved.
Keywords: Entrepreneur; Entrepreneurship; Entrepreneurship profiles; Entrepreneurship training